Youth Language in Digital Communication: on How to Sell Drugs Online (fast) - Robles Sabater, Ferran (Revista de Filología Alemana, 2024)
This paper intends to examine how the characteristic features of electronic communication among young people are recreated in the German fiction TV series How to sell drugs online (fast). It presents the results of the analysis of 108 conversations held by its characters on social networks, instant messaging applications, video games and internet platforms. The research has allowed to identify recurring linguistic mechanisms, which have been classified into six different levels: lexical-semantic, morphosyntactic, orthotypographic, pragmatic, visual and medial. All of them help to evoke the kind of conceptional orality that colloquial conversations maintained through these digital media typically reproduce and, consequently, to give verisimilitude to the plot as well as to the characters.
Keywords: youth language; colloquial language; conceptional orality; communicative immediacy; Digital Media